Efficacy of functional rehabilitation on dynamic balance in athletes with lateral ligament ankle injury - Deivendran, Kalirathinam; Hairul Anuar, Hashim; Taran, Singh; Mohamed Saat, Ismail (2017)
The aim of the present study was to construct an integrated rehabilitation exercise program to improve dynamic balance in cases of grade II lateral ligament ankle injury. Fifty-Two (30 female and 22 male) athletes who required functional strength exercises due to grade II lateral ligament ankle injury and they were randomly assigned to four groups. The Group A received conventional physiotherapy training, Group B received BOSU exercise training, Group C received Neuromuscular training, Group D receive combination of group B + C (BOSU Exercise training and Neuromuscular training) for 12 weeks. A 12-week rehabilitation training program was constructed with the aim of improving dynamic balance of the lower limb. Dynamic balance was evaluated using the Y Balance Test were measured before and after the 12-week program. Following 12 weeks of rehabilitation program, there were statistically significant improvements in the ratios of dynamic balance in subjects received combination of BOSU exercise training and neuromuscular training. The rehabilitation exercise program for grade II lateral ligament ankle injury helped to restore normal joint range of motion, muscle strength and endurance, and functional ability.